2015
DOI: 10.1093/jmammal/gyu021
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history of the sableMartes zibellina(Mammalia, Carnivora) on the marginal peninsula and islands of northeastern Eurasia

Abstract: We examined the nucleotide sequences of the mitochondrial NADH dehydrogenase subunit 2 gene (976 base pairs) for 279 individuals of the sable Martes zibellina (Carnivora, Mustelidae), derived from diverse areas throughout the regions of the Ural Mountains to the Russian Far East on the Eurasian continent and the peripheral peninsula (Kamchatka) and islands (Sakhalin, Hokkaido, and southern Kurils). The demographic history of the sable and its migration history to the eastern peripheral peninsula and islands we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 92 publications
1
22
0
1
Order By: Relevance
“…Low genetic diversity is predicted to lead to extinction through inbreeding and/or by limiting immunological and evolutionary capabilities to cope with changing environments (Hughes and Stachowicz, 2004;Frankham et al, 2010). In fact, threatened species tend to have lower levels of genetic diversity (Frankham, 1996;Spielman et al, 2004), and the genetic diversity of small island populations has been reported to be lower than those of populations on nearby larger land masses (e.g., White and Searle, 2007;Sato et al, 2009;Kinoshita et al, 2015). However, the associations between limited genetic variation and island areas are not yet fully understood, especially with respect to mammals (White and Searle, 2007; see also Frankham, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Low genetic diversity is predicted to lead to extinction through inbreeding and/or by limiting immunological and evolutionary capabilities to cope with changing environments (Hughes and Stachowicz, 2004;Frankham et al, 2010). In fact, threatened species tend to have lower levels of genetic diversity (Frankham, 1996;Spielman et al, 2004), and the genetic diversity of small island populations has been reported to be lower than those of populations on nearby larger land masses (e.g., White and Searle, 2007;Sato et al, 2009;Kinoshita et al, 2015). However, the associations between limited genetic variation and island areas are not yet fully understood, especially with respect to mammals (White and Searle, 2007; see also Frankham, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, previous studies of other mammalian species also suggested possible refugia in the Ural Mountains. For example, the sables ( Martes zibellina Linnaeus, 1758; Kinoshita et al, ) and the bank voles ( Myodes glareolus Schreber, 1780; Deffontaine et al, ) from the Ural Mountains had relatively higher genetic diversities, suggesting the polymorphic status of relict populations of them. The Ural Mountains were reported as refugia for the common shrews ( Sorex araneus Linnaeus, 1758) by Polyakov et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Three calibration points were set on the basis of the divergence times among outgroup species and least weasels. Following Sato et al () and Kinoshita et al (), a normal distribution with a mean of following time and SD was adopted to this analysis: 5.985 ± 0.315 million years ago (mya) between M. nudipes and the others, 5.365 ± 0.195 mya between M. kathiah and the others except M. nudipes, and 3.685 ± 0.285 mya between M. erminea and M. nivalis . In addition, the published estimate of least weasel mtDNA Cytb substitution rate of 2.1% Myr −1 from Dawson, Hope, Talbot, and Cook () and the strict clock model were also used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Проведенные подробные исследования морфологии соболя [13,14,20] описали изменчивость по ареалу, не привели к единому мнению о современной подвидовой структуре вида, но при этом показали, что «наблюдаемая картина изменчивости признаков на ареале повто-ряет процесс формирования морфологического облика популяций в ходе постгляциальной радиации» [11]. Молекулярно-генетические исследования митохондриальных и ядерных локусов позволили рассмотреть географическую изменчивость в ареале, филогеографию и историю расселения [10,15,2], в том числе заселение тихоокеанских островных систем [18]. Анализ микросателлитных локусов позволил получить представление о генетической структуре вида в целом, с выявлением особенностей популяций крупных пространственно разобщенных географических регионов [8,12].…”
Section: Introductionunclassified